2020
DOI: 10.3390/antibiotics9060287
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Mutation in DNA Gyrase and Changes in the Fluoroquinolone Resistance of Helicobacter pylori over a 14-Year Period: A Single Center Study in Korea

Abstract: The efficacy of fluoroquinolone-based eradication therapy largely depends on the fluoroquinolone resistance of H. pylori. The aim of this study was to investigate the changes in the primary resistance rate of H. pylori to fluoroquinolone and the mechanism of resistance in Korea. A total of 153 strains and 48 strains of H. pylori were isolated at a tertiary hospital in 2005/2006 and 2017/2018, respectively. The minimum inhibitory concentrations (MICs) of fluoroquinolone were determined by the serial 2-fold agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…LEV resistance rate of 11% was detected in Morocco by Bouihat et al [ 23 ] in a multicenter study of patients who had never been treated previously. Interestingly a recent article [ 27 ] dealing with a study in Korea reports a new mutation of gyrA (a novel Gly-85 mutation of gyrA ) different from those we have examined in our research, conferring resistance to fluoroquinolones. In this case, the authors found that the resistance rates increased from 19.0% to 43.8% both for levofloxacin and moxifloxacin.…”
Section: Discussionmentioning
confidence: 64%
“…LEV resistance rate of 11% was detected in Morocco by Bouihat et al [ 23 ] in a multicenter study of patients who had never been treated previously. Interestingly a recent article [ 27 ] dealing with a study in Korea reports a new mutation of gyrA (a novel Gly-85 mutation of gyrA ) different from those we have examined in our research, conferring resistance to fluoroquinolones. In this case, the authors found that the resistance rates increased from 19.0% to 43.8% both for levofloxacin and moxifloxacin.…”
Section: Discussionmentioning
confidence: 64%
“…The main antibiotics used for H. pylori eradication, the resistance mechanisms and the main resistance biomarkers are briefly reviewed below and are summarized in Table 2. [156,159,[168][169][170] * Exemplificative studies targeting the mentioned biomarker are referred.…”
Section: Genes Involved In Antibiotic Resistancementioning
confidence: 99%
“…The most common mutations occur on the quinolone resistance-determining region (QRDR) of gyrA affecting codons 91 and 87 of the gyrA product, more specifically D91 to G [149,159,165,168], N [150,165,168,169,200] or Y [150,165,168] and N87K [150,159,165,168,201]. Despite this, changes in other codons of both gyrA, and, less frequently, gyrB products were, and continue to be, frequently reported, although the impact of some of them on antibiotic resistance is not yet well established [168,171,200]. Alternative mechanisms have not been described but were suggested to exist [165,168,171].…”
Section: Levofloxacinmentioning
confidence: 99%
See 2 more Smart Citations